The Importance of Organizational Support in Preventing Obesity Among Nurses in Hospitals - Rio Verdiansyah; Hanny Handiyani; Tuti Afriani; Novieastari Novieastari; Andi Amalia Wildani; Joan Xaveria Mahulae (Indonesian Journal of Global Health Research, 2026)
Obesity in nurses is a growing occupational health problem and has implications for the quality of service and patient safety. Organizational support is seen as an important resource within the nursing management framework that can shape a health-promoting work environment and lower the risk of obesity. To analyze the relationship between organizational support and the incidence of obesity in nurses in hospitals. A quantitative study with a cross-sectional design was conducted on 227 nurses in a teaching hospital by 2025 nurses were selected as the sample using a purposive sampling technique. Obesity status is determined based on Body Mass Index (BMI). Organizational support was measured using a structured questionnaire that has been tested for validity and reliability. The analysis was carried out in univariate, bivariate, and multivariate logistic regression with a significance level of p < 0.005. The prevalence of obesity in nurses was 57.3%. Bivariate analysis showed that organizational support was significantly related to obesity incidence (p < 0.005). In a multivariate analysis, nurses with low organizational support were 5.582 times more likely to be obese than nurses with good organizational support (OR = 5.582; 95% CI: 2.064–15.094; p = 0.001), after controlling for confounding variables. Organizational support is a strong independent determinant of obesity in nurses.